Abortion Law in Indonesia: Reconciling Criminal Justice, Islamic Law, and Human Rights - Dinda Ayu Arini Chaniago; Noor Azizah (Yayasan Lembaga Studi Makwa, 2026)
This study aims to analyze abortion law in Indonesia through the perspectives of criminal justice and Islamic law, particularly following the enactment of Law Number 1 of 2023 concerning the Indonesian Criminal Code. The study examines the legal construction of abortion offences, the criminal regulation established under Indonesia’s new Criminal Code, and the extent to which these provisions correspond with Islamic legal principles and human rights considerations. This research employs a normative juridical method using statutory and conceptual approaches, supported by library research involving the analysis of primary legal materials, including legislation and Islamic legal sources, as well as secondary materials consisting of scholarly works and academic studies on abortion regulation. The findings demonstrate that Indonesian criminal justice maintains abortion as a prohibited act subject to criminal sanctions while providing limited legal exceptions for pregnancies resulting from rape or sexual violence and for medical emergencies. From the perspective of Islamic law, these exceptions may be accepted when they fulfil the principles of necessity and are consistent with the objectives of maqasid al-shari’ah, particularly the preservation of life (hifz al-nafs) and the preservation of progeny (hifz al-nasl). The study concludes that abortion regulation in Indonesia represents a legal reform effort aimed at balancing criminal responsibility, Islamic legal values, and human rights protection. This research contributes academically by enriching the discourse on abortion law reform and demonstrating how criminal justice and Islamic law interact in addressing reproductive issues within a contemporary legal system.